VD_FINDINFO Arrêt / 2012 / 158 vom 16. Januar 2012 - VD Tribunal cantonal (2012)
RELATIONS PERSONNELLES, MESURE PROVISIONNELLE, SUPPRESSIONEN GÉNÉRAL | 273 CC, 314 ch. 1 CC, 420 al. 2 CC, 489 CPC, 29 al. 2 Cst.